PENERAPAN MEDIA BERBASIS AUDIO VISUAL UNTUK MENINGKATKAN PEMAHAMAN TATA CARA WUDHU PADA PELAJARAN FIQIH Penelitian Tindakan Pada Siswa Kelas 1 Di TPQ Al-Hasan Pakuluran Kabupaten Sumedang - Hasan Khoerudin; Enjen Abdul Zaeni (CV. AFDIFAL MAJU BERKAH, 2026)
This study aims to improve the understanding of wudhu procedures among first-grade students at TPQ Al-Hasan through the application of audio-visual-based media. The research was motivated by the low level of student understanding, where 10 out of 11 students (91%) had not achieved mastery in the wudhu material due to traditional teaching methods. This Classroom Action Research (CAR) was conducted in two cycles, following the participatory PTK model. Data collection techniques included observation, interviews, and documentation. The results showed a significant improvement. The average student understanding score increased from 68.5 in Cycle I to 78.90 in Cycle II. The classical learning mastery percentage also jumped from 42.6% to 100%. Furthermore, student activity and participation in learning increased from 73% (Good) to 82% (Very Good). The study concludes that audio-visual media is effective in significantly improving students’ understanding, engagement, and learning outcomes on wudhu procedures. Therefore, it is recommended that teachers implement this media and that future researchers test its effectiveness in different contexts and with broader subjects.